Sistem Teknologi Informasi Dalam Rintisan Desa Tangguh Bencana - Muhamad Muhamad (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
Disaster Resilient Village is a formation program of rural communities to be more self-sufficient in the face of the disaster that struck the village. The program is conducted in villages considered vulnerable to disasters. The method will be implemented in the form of community development activities Rural Information System based on information technology with community participation in solving any problems through mutual discussions. They will also be carried out disaster management including the completion of a structural nature disaster and evacuation route tool. The execution of community development programs through this information system will also be supported by partners from institutions related to each issue. The research aims to: a) the public has the readiness to face the threat of natural disasters in terms of both facilities and infrastructure as well as in terms of human resources; b) empowerment does not occur during a disaster will be able to improve the human development index (HDI) is based on the economic, health, and education; c) the public is able to carry out mitigation and recovery measures independently without having to rely on government assistance when it occurs. The conclusion target group applying Appropriate Technology Information System (Community Based Information Network) Disaster Resilient Village. Results showed that community participation is very high and isable to operationalize SID.